Person‐centered assessment of apathy and resistance to care in people living with dementia: Review of existing measures - Benjamin T. Mast; Emilee M. Ertle; Ann Kolanowski; Gail Mountain; Esme Moniz‐Cook; Margareta Halek (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction The review described in this paper builds upon the Dementia Care Practice Recommendations (DCPR) published by the Alzheimer's Association in 2018 and addresses behavior change and the need for targeted outcome measures that evolve from person‐centered frameworks and help evaluate interventions. Apathy and resistance to care (RTC) are two specific behavioral expressions of unmet need or distress exhibited by people living with dementia, which are upsetting to formal and family caregivers and compromise quality of life for people living with dementia. Methods We conducted literature searches of major databases (PsycInfo, PubMed, EBSCO, CINAHL) for papers examining apathy and RTC constructs in samples of people living with dementia. Reliability and validity coefficients were reviewed and reported, along with examination of whether each measure facilitates contextual understanding of behavior. Results Three stand‐alone measures of RTC and ten measures of apathy were identified and reviewed. The RTC measures demonstrated good psychometric properties but do not include the perspective of the person living with dementia or contextual aspects of the behavior. The identified apathy measures demonstrated fair to good psychometric properties, and although there is greater consideration of context, none adequately include the perspective of the person living with dementia. Discussion Although reliable and valid measures have been developed to measure apathy and RTC in people living with dementia, there is greater need for conceptually driven measurement of behavior context and for tools that elicit and include the perspective of the person living with dementia.